Sensitive time-resolved fluoroimmunoassay for the quantitative detection of okadaic acid - Qin, Yuan; Li, Jiayu; Kuang, Jiani; Shen, Sicheng; Jiang, Jingwen; Zhang, Zhi; Zhao, Chenhao; Zhou, Xiumei; Huang, Biao; Han, Bingnan (Frontiers in Marine Science, 2022)
Okadaic acid (OA) is a biotoxin from marine microalgae and widely present in shellfish, which severly affects the seafood safety. Therefore, it is essential to establish a highly sensitive OA analysis and detection method. In this study, a new type of immunoassay technology was established on the basis of the competition method using time-resolved fluoroimmunoassay (TRFIA). OA-bovine serum albumin (OA-BSA) coated on a 96-well plate competes with OA standard or samples to bind OA antibodies. A rare-earth ion-labeled secondary antibody, which fluoresces strongly under the effect of the enhancement solution, was then added as a tracer for detection. The established linear range of OA detected by TRFIA was 2.49 ⅹ 10-3 – 50 ng/mL, and the limit of detection was 2.49 ⅹ 10-3 ng/mL. The average coefficients of variation from intra-assay and inter-assay batches were 3.34% and 5.87%, respectively, and the recovery rate was 93.04% – 111.66%. The OA in shellfish samples was determined by TRFIA and high-performance liquid chromatography (HPLC), and the results showed a good correlation. This study established a TRFIA to detect OA, which has the characteristics of simplicity, sensitivity, precision, and high accuracy, far exceeding the EU or US standards for the detection of shellfish toxins. It is expected to make proper contribution in marine biotoxin detection.